Sustainable urbanism and urban form: articulations and perspectives - Alvarez, Lucas Tasso; Soares, Beatriz Ribeiro (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
Urban space has been a scene of numerous political, social, and technological transformations during the last two centuries. As a result of an intense process of population and territorial growth of cities, urban fabrics around the world are marked by socio-spatial conflicts, which puts them in a particular urban crisis. As an opposing view, the concept of sustainable urbanism arises, resignifying the paradigmatic urban problems. However, it is a concept of complex definition, both theoretical and, mainly, practical. With the problem based on the development of the praxis of sustainable urbanism, this article aims to discuss aspects of urban form that contribute to the applicability of sustainable urbanism. The paper uses an exploratory methodology as to its objectives and follows a bibliographical research model as to its design. Due to the association proposed, the results indicate the combination of the following morphological principles in the city as desirable elements for urban sustainability: multifunctionality, compactness, connectivity, diversity, access to nature, and definition. The combination of these principles leads to the self-sustainability of the urban space. The article has the potential to contribute to researchers and practitioners scientifically and to assist in the implementation of sustainable cities.